Everyday discrimination among formerly homeless persons in permanent supportive housing. Issue 2 (3rd July 2019) - Wenzel, Suzanne L.; Rhoades, Harmony; LaMotte-Kerr, Wichada; Duan, Lei
ABSTRACT: Experiences of discrimination are associated with poor health and are particularly common among persons experiencing homelessness. Permanent supportive housing (PSH) provides a foundation for improved well-being among persons with homelessness histories, but research on discrimination among this population is limited. We examined changes in experiences of, and perceived reasons for, everyday discrimination when persons moved into PSH. 421 adults in Los Angeles County completed baseline (pre-housing), 3-, 6- or 12-month post-housing structured interviews. Generalized linear mixed models (GLMM) examined change in discrimination outcomes, controlling for demographic characteristics. Everyday discrimination experiences decreased significantly when persons moved from homelessness into PSH, and remained consistently lower across the first year in PSH. Reports of homelessness/poverty, race/ethnicity, and neighborhood as reasons for discrimination also decreased from baseline levels. PSH may offer respite from everyday discrimination, but the persistence of discrimination and particularly racism in society requires structural solutions addressing implicit bias and systemic inequities.